Immune Activation in Primary Human Immunodeficiency Virus: Influence of Duration of Infection, Treatment, and Substance Use. (24th March 2022) - Gilada, Trupti; Schnittman, Samuel R; White, Edward; Mercader, Jacqueline; Wang, Yixin; Dasgupta, Sayan; Valdez, Rogelio; Pinto-Santini, Delia; Pasalar, Siavash; Sanchez, Jorge; Gonzales, Pedro; Lama, Javier R; et al.
Abstract: Background: Primary human immunodeficiency virus (HIV) is characterized by dynamic changes in viral load and innate and adaptive immune responses; it is unclear the extent to which time from acquisition to antiretroviral therapy (ART) initiation and substance use impact these immunologic changes. Methods: We studied plasma immune activation biomarkers, viral load, and CD4 + and CD8 + cell counts in participants from the Sabes primary infection study in Peru, who had been randomized to begin ART immediately after diagnosis vs 24 weeks later. We modeled influence of substance use and duration of HIV infection on biomarkers at baseline and over 24 weeks. Results: Compared to participants enrolled >30 days after HIV acquisition, participants enrolled during acute infection (≤30 days) had higher mean interferon (IFN)–γ and IFN-α2a (1.7-fold and 3.8-fold interquartile range [IQR] higher, respectively). Participants enrolled >30 days after HIV acquisition had higher mean baseline CD8 + cell count (2.7 times the IQR). Alcohol use (positive phosphatidylethanol level) was associated with elevated IFN-γ, tumor necrosis factor alpha (TNF-α), and interleukin 12p70 (IL-12p70), and smoking was associated with higher macrophage inflammatory protein 1α, TNF-α, and IL-12p70. Most biomarkers declined more quickly in participants who initiated ART immediately; however, substance use and duration of HIV infection at enrollment had little influence on rate of decline. Conclusions: IFN-γ and other biomarkers are elevated during early primary infection, when exposure to HIV antigens is high. Immune activation decreased most quickly in those who started ART during acute/early primary infection. Higher CD8 + cell counts and a trend toward higher soluble CD163 levels during the 30 days after acquisition suggest the onset of compensatory responses and immune exhaustion. Abstract : Most markers of immune activation were higher during acute HIV infection vs later in primary infection. Decline in activation markers was associated with time of antiretroviral therapy initiation, with little impact of alcohol use or smoking.